Electrophoretic variants of L-amino acid oxidase in geographically separated populations of Neurospora - W. L. Chan; C. C. Ho (Fungal Genetics Reports, 1973)
Electrophoretic variants of L-amino acid oxidase in geographically separated populations of Neurospora